Mutations in the genes encoding 11beta-hydroxysteroid dehydrogenase type 1 and hexose-6-phosphate dehydrogenase interact to cause cortisone reductase deficiency. - Draper, N; Walker, E; Bujalska, I; Tomlinson, J; Chalder, S; Arlt, W; Lavery, G; Bedendo, O; Ray, D; Laing, I; Malunowicz, E; White, P; et al. (2003)
In cortisone reductase deficiency (CRD), activation of cortisone to cortisol does not occur, resulting in adrenocorticotropin-mediated androgen excess and a phenotype resembling polycystic ovary syndrome (PCOS; refs. 1,2). This suggests a defect in the gene HSD11B1 encoding 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), a primary regulator of tissue-specific glucocorticoid bioavailability. We identified intronic mutations in HSD11B1 that resulted in reduced gene transcription in three individuals with CRD. In vivo, 11beta-HSD1 catalyzes the reduction of cortisone to cortisol whereas purified enzyme acts as a dehydrogenase converting cortisol to cortisone. Oxo-reductase activity can be regained using a NADPH-regeneration system and the cytosolic enzyme glucose-6-phosphate dehydrogenase. But the catalytic domain of 11beta-HSD1 faces into the lumen of the endoplasmic reticulum (ER; ref. 6). We hypothesized that endolumenal hexose-6-phosphate dehydrogenase (H6PDH) regenerates NADPH in the ER, thereby influencing directionality of 11beta-HSD1 activity. Mutations in exon 5 of H6PD in individuals with CRD attenuated or abolished H6PDH activity. These individuals have mutations in both HSD11B1 and H6PD in a triallelic digenic model of inheritance, resulting in low 11beta-HSD1 expression and ER NADPH generation with loss of 11beta-HSD1 oxo-reductase activity. CRD defines a new ER-specific redox potential and establishes H6PDH as a potential factor in the pathogenesis of PCOS.